(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article addresses so-called "body arts", covering discussions on performing arts, choreography and performance art, drafting a concept for the word "exhibit", proposing it as a measure for control levels on the exhibition and enjoyment of works on these fields. The hypothesis is that performance art, today, is the language in which the exhibition elements engender themselves best suited for what defines the word "exhibit". Transversally, it also addresses questions related to curating and exhibition design, paradigm changes on the presence of human body on arts and the creation of aesthetic meaning from the materiality of the very elements forming the artwork.